Ocenjevanje učinkovitosti rehabilitacijske obravnave bolnic po raku dojke v termah Dobrna - Kotnik, Annemary (Rehabilitacija (Ljubljana), 2018)
Background: Breast cancer is the most common cancer in women. The incidence of breast cancer is rising, as well as the survival rate, therefore, appropriate early, advanced and late rehabilitation is needed. In the advanced rehabilitation in Slovenia14-day spa treatment also included. The aim of our study was evaluation of the effectiveness of rehabilitation in the spa, namely the range of motion of the shoulder, the upper limb function and the quality of life of patients after breast cancer. Methods: In 9 months we included in the study 93 patients after breast cancer operation. A total of 89 patients completed the 14-day rehabilitation in the spa. 76 patients correctly filled in questionnaires. We obtained data on patient age, date of operation, type of surgery and additional therapy, range of motion of the shoulder, function of the upper extremity and shoulder using SPADI and DASH questionnaires and quality of life using the EORTC QLQ-C30 questionnaire and EORTC QLQ-BR23 breast cancer module. A good outcome of rehabilitation was assessed in case when there was a statistically significant improvement in range of motion of the shoulder, upper limb function and quality of life. Results: The average age of breast cancer patients included in the study was 52,8 years. There were no statistically significant differences between groups in the range of motion in the shoulder, upper limb function and quality of life, prior to the commencement of rehabilitation. After rehabilitation, there was a statistically significant improvement in all three groups, both in the range of motion of the shoulder (p<0.001), upper limb function (p<0.001) and quality of life (p<0.001). We did not find statistically significant differences in improvement between the groups. Conclusion: The type of breast cancer surgery did not affect the quality of life before and after rehabilitation. After the team rehabilitation at the health resort, all groups improved in the quality of life and ultimate functional status of the patients. However, to validate our results, further research with a larger sample is needed.
Keywords: breast cancer; Breast Neoplasms; gibljivost rame; kvaliteta življenja; quality of life; rak dojke; rehabilitacija; rehabilitation; shoulder motion; upper limb; vocational rehabilitation; zgornji ud